BUAH BIT (BETA VULGARIS) DAN KENAIKAN HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA : SYSTEMATIC REVIEW - Rina Tri Handayani; Verantika Dewi Saraswati; Anggie Pradana Putri (STIKES Pemkab Purworejo, 2024)
Background: Anemia is a common health issue among pregnant women worldwide, especially in developing countries. To address anemia, it can be tackled through two approaches: pharmacologically via iron tablet consumption and non-pharmacologically through beetroot (Beta vulgaris) consumption. Objective: This Systematic Review aims to analyze the effectiveness of beetroot supplementation in increasing hemoglobin levels among pregnant women with anemia. Methods: This study employed a systematic review method. Articles were searched in Google Scholar and PubMed databases for publications within the last five years (2020-2024), using the PICO approach (Population: pregnant women; Intervention: beetroot supplementation; Comparator: no beetroot supplementation, non-anemic; Outcome: increase in hemoglobin levels). The article selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The selected articles were then assessed for their eligibility using the Joanna Briggs Institute (JBI) Checklist. Results: Literature review findings indicate that beetroot consumption can effectively increase hemoglobin levels in pregnant women with anemia. The average increase in hemoglobin levels after beetroot intervention ranged from 0.6 to 2.0 g/dL. Combination therapy involving beetroot with lemon, honey, or dates also showed significant improvements in hemoglobin levels, but beetroot supplementation as a single therapy yielded a hemoglobin increase of up to 2.54 g/dL. Conclusion: Beetroot consumption proves to be effective in increasing hemoglobin levels in pregnant women with anemia. This intervention can serve as a safe and natural alternative in managing anemia during pregnancy.